Investigation into the Seed-Borne Nature and seed to Seedling Transmission of Phytophthora in Cocoa (Journal of Science and Technology, 2016)
The study verified a report that Phytophthora spp., causing black pod disease of cocoa in Ghana, are seed-borne and systemically transmitted to seedlings. To demonstrate seed borne nature, seeds from healthy and diseased cocoa pods were assayed for Phytophthora spp. Seed to seedling transmission was studied by artificially inoculating visually healthy seeds with P. palmivora, incubating the seeds in humidified Petri dishes, sowing in plastic cups and biopsying parts of the emerging seedlings for the fungus. Uninoculated seeds were sown as controls. Mature seedlings from a farmer's nursery and seedlings from seeds of naturally diseased pods were also assayed. All 1,028 seeds from healthy pods were free of Phytophthora. In contrast, 63% of seeds from diseased pods harboured the fungus. Detection of Phytophthora from the various components of infected seeds was highest for the mucilage/testa (57% detection frequency,) followed by the embryo (38%) and cotyledon (37%). Phytophthora palmivora was detected in rhizosphere soils, roots, stem bases, undetached cotyledons and testas of undetached cotyledons of seedlings from artificially infected seeds. It was absent from the middle and upper portions of stems as well as from leaves of such seedlings. Similar results were obtained with naturally infected seeds. The fungus was neither detected in farmer seedlings nor in seedlings of uninoculated seeds. It is concluded that systemic transmission of Phytophthora from the cocoa seed to the leaves of seedlings is impossible.